Smart Village Initiative in Indonesia: Governance’s Perspective Using PESTLE Analysis - Pinuji, Sukmo; Lestari, Novita Dian; Yudhistira, Muhamad Irfan (Tunas Agraria, 2024)
Globally, including in Indonesia, people have adopted the Smart Village Initiative. Although beneficial, the integration of information and communication technology (ICT) creates complexity in rural areas. The implementation of Smart Village varies due to different geographic, demographic, economic, and social backgrounds. Land-based implementations overcome challenges due to the dynamic nature of spatial data and attributes associated with land parcels, requiring an understanding of surveying as well as mapping for data updates and maintenance. This research aims to understand how these variations influence the implementation of smart villages and identify factors that impact the initiative. Using a comparative study approach, we analyzed the implementation of the Smart Village initiative in two different areas and assessed the results using the PESTLE analysis tool. The findings show that economic and social factors play an important role in shaping the design characteristics of the Smart Village, thereby creating significant differences between the two villages. These factors shape the inclusion of specific modules in the application. However, both face challenges related to community involvement, ICT culture, and environmental factors, which have an impact on optimizing utilization to achieve wider coverage and awareness in ICT adaptation.   Inisiatif Desa Cerdas diadopsi secara global, termasuk di Indonesia. Meskipun bermanfaat, integrasi Teknologi Informasi dan Komunikasi (TIK) menimbulkan kompleksitas di pedesaan. Penerapan Smart Village bervariasi karena latar belakang geografis, demografi, ekonomi, dan sosial yang berbeda. Implementasi berbasis tanah menghadapi tantangan karena sifat dinamis dari data spasial dan atribut yang terkait dengan bidang tanah, sehingga membutuhkan pemahaman survei serta pemetaan untuk pembaruan dan pemeliharaan data. Penelitian ini berupaya untuk memahami bagaimana variasi-variasi tersebut mempengaruhi pelaksanaan inisiatif Desa Cerdas dan mengidentifikasi faktor-faktor yang memberikan dampak terhadap inisiatif tersebut. Dengan menggunakan pendekatan studi komparatif, kami menganalisis implementasi inisiatif Desa Cerdas di dua bidang berbeda dan menilai hasilnya dengan menggunakan alat analisis PESTLE. Temuan menunjukkan bahwa faktor ekonomi dan sosial memainkan peran penting dalam membentuk karakteristik desain Desa Cerdas, sehingga menciptakan pembeda yang signifikan antara kedua desa tersebut. Faktor-faktor ini terutama mempengaruhi modul spesifik mana yang akan disertakan dalam aplikasi. Namun keduanya menghadapi tantangan terkait keterlibatan masyarakat, budaya TIK, dan faktor lingkungan, yang berdampak pada optimalisasi pemanfaatan untuk mencapai cakupan dan kesadaran yang lebih luas dalam adaptasi TIK.